Ornamental Ficus Diseases: Identification and Control in Commercial Greenhouse Operations - David J. Norman; Shad Ali (EDIS)
While edible figs are grown agronomically for delicious fruit, many Ficus species have been commercialized for decorative, ornamental purposes. These horticultural Ficus varieties are used for interiorscape houseplant décor and for outdoor landscape design. This article provides guidelines for the identification and treatment of diseases that may be encountered during the commercial production of ornamental Ficus. This 7-page fact sheet was written by D. J. Norman and Shad Ali, and published by the UF Department of Plant Pathology, August 2013.